Academic Stress and Insomnia in Adolescents - Ririn Rindiani; Umi Faridah; Dewi Hartinah (Sarana Ilmu Indonesia (salnesia), 2026)
Academic stress is one of the psychological problems that teenagers often experience and can affect sleep quality to cause insomnia. This study aimed to determine the relationship between academic stress and insomnia in adolescents at SMA Muhammadiyah Kudus. The study used a quantitative analytical design with a cross-sectional approach. The research sample was 170 subjects from grades 10 and 11 who were selected using purposive sampling techniques. Data collection used the Educational Stress Scale for Adolescents (ESSA) questionnaire to measure academic stress and the Insomnia Severity Index (ISI) to measure insomnia levels. Data analysis was carried out using the Spearman Rank test. The results showed that the majority of subjects were 16 years old, female, and from grade 10. Most of the subjects experienced severe category insomnia as many as 118 subjects (69.4%). The academic stress level of subjects was mostly in the medium category as many as 86 subjects (50.6%), while the high category was 79 subjects (46.5%). The results of the Spearman Rank test showed a significant relationship between academic stress and insomnia in adolescents with a value of p = 0.001 (p-value < 0.05) and a correlation coefficient of r = 0.368 which showed a positive association with moderate strength. The results of the regression analysis showed a determination coefficient value (R²) of 13.5%, which meant that academic stress contributed 13.5% to the incidence of insomnia in adolescents.